Selective screening for familial hypercholesterolemia in Austrian children - first year results - Alexandra Kreissl; Nina Walleczek; Pinky Rose Espina; Ulrike Hallwirth; Susanne Greber-Platzer (BMC, 2019)
Abstract Background Familial hypercholesterolemia (FH), the most frequent monogenetic hereditary disorder, is underdiagnosed and undertreated. Early identification of FH is essential because of the increased risk for premature cardiovascular diseases and childhood might be the optimal period for cholesterol screening. Aim of this selective screening was to detect familial hypercholesterolemia, the most frequent monogenetic hereditary disorder in children to guarantee early detection and treatment. The Austrian strategy for primary schools, to perform a pre-school examination by school physicians, allows to reach all children aged 5-7 years. Methods The screening was conducted within the school enrolment examinations in all 215 public primary schools in Vienna between January to May 2017. Positive cholesterol screening was defined by non-HDL-C > 160 mg/dL and/or LDL-C > 130 mg/dL. Results In total, 18,152 children had their school enrolment examination. From 133 tested pre-school children, nine individuals were positive-screened with a mean LDL-C of 161 ± 26 mg/dL, non-HDL-C of 181 ± 24 mg/dL and total cholesterol (TC) of 239 ± 23 mg/dL. From 85 siblings, four individuals were positively screened with a mean LDL-C of 150 ± 7 mg/dL, non-HDL-C of 184 ± 8 mg/dL and TC of 231 ± 10 mg/dL. Patients did not have any xanthomas, xanthelasms, arcus lipoides, or any cardiovascular comorbidities. Conclusions Screening at early childhood by school physicians seems to be a successful strategy and possible. With this Austrian selective screening method, FH Kids Austria, we could find nine patients with positive raised level LDL-cholesterol and/or non-HDL cholesterol out of 133 blood tests. Prevention of cardiovascular diseases is essential and it is our duty to increase the awareness of this disease. Limitations of the FH Kids project were reduced participation of school physicians and refusal of the parents.